Histone modifications underlie monocyte dysregulation in patients with systemic sclerosis, underlining the treatment potential of epigenetic targeting. Issue 4 (6th February 2019) - van der Kroef, Maarten; Castellucci, Monica; Mokry, Michal; Cossu, Marta; Garonzi, Marianna; Bossini-Castillo, Lara M; Chouri, Eleni; Wichers, Catharina G K; Beretta, Lorenzo; Trombetta, Elena; Silva-Cardoso, Sandra; Vazirpanah, Nadia; et al.
Abstract : Background and objective: Systemic sclerosis (SSc) is a severe autoimmune disease, in which the pathogenesis is dependent on both genetic and epigenetic factors. Altered gene expression in SSc monocytes, particularly of interferon (IFN)-responsive genes, suggests their involvement in SSc development. We investigated the correlation between epigenetic histone marks and gene expression in SSc monocytes. Methods: Chromatin immunoprecipitation followed by sequencing (ChIPseq) for histone marks H3K4me3 and H3K27ac was performed on monocytes of nine healthy controls and 14 patients with SSc. RNA sequencing was performed in parallel to identify aberrantly expressed genes and their correlation with the levels of H3K4me3 and H3K27ac located nearby their transcription start sites. ChIP-qPCR assays were used to verify the role of bromodomain proteins, H3K27ac and STATs on IFN-responsive gene expression. Results: 1046 and 534 genomic loci showed aberrant H3K4me3 and H3K27ac marks, respectively, in SSc monocytes. The expression of 381 genes was directly and significantly proportional to the levels of such chromatin marks present near their transcription start site. Genes correlated to altered histone marks were enriched for immune, IFN and antiviral pathways and presented with recurrent binding sites for IRF and STAT transcription factors at their promoters. IFNα induced the binding of STAT1 and STAT2 at the promoter of two of these genes, while blocking acetylation readers using the bromodomain BET family inhibitor JQ1 suppressed their expression. Conclusion: SSc monocytes have altered chromatin marks correlating with their IFN signature. Enzymes modulating these reversible marks may provide interesting therapeutic targets to restore monocyte homeostasis to treat or even prevent SSc.